Does Preoperative Orientation and Education Alleviate Anxiety in Posterior Spinal Fusion Patients? A Prospective, Randomized Study. Issue 3 (April 2015) - Rhodes, Leslie; Nash, Cassie; Moisan, Alice; Scott, Donna C.; Barkoh, Kaku; Warner, William C.; Sawyer, Jeffrey R.; Kelly, Derek M.
Abstract : Background: A prospective, randomized study examined the effect of interventional preoperative education and orientation for scoliosis surgery (PEOSS) on anxiety levels of patients undergoing posterior spinal fusion (PSF). Secondary outcomes analyzed were caregiver anxiety, length of stay, morphine equivalent usage, and patient/caregiver satisfaction. Methods: Patients undergoing PSF were randomly distributed into a control group (N=39) or interventional group (N=26). All subjects and caregivers completed the State (current)-Trait (typical) Anxiety Inventory (STAI) at different intervals: preoperative appointment, preoperative holding area, postoperative orthopaedic unit, and discharge. At discharge, patients and caregivers completed a satisfaction survey. Results: Significantly higher state anxiety scores were found compared with baseline at all time intervals in both the control group and PEOSS group. The PEOSS group had higher state anxiety scores than the control group at the postoperative interval ( P =0.024). There were no significant differences in the caregiver state anxiety scores between the groups at any time interval. Trait anxiety scores for both groups remained stable over time, establishing that the measurement tool accurately reflected baseline anxiety. No significant differences were found in length of stay or morphine equivalent use. Patient satisfaction scores were higher in the PEOSS group than in the control group ( P =0.0005). Conclusions: PSF was associated with increased anxiety at all time intervals in adolescents in both groups. In the PEOSS group, PSF was associated with increased anxiety in the immediate postoperative period. Despite the increase in anxiety, patient satisfaction was higher in the intervention group. It is likely that patients need age-appropriate information and educational strategies to minimize anxiety during PSF. Further work is underway to study and develop more effective interventional strategies. Level of Evidence: Level I study.